Drought resilience demands urgent global actions and cooperation - Stefanski, R.; Toreti, A.; Aich, V.; Hagenlocher, M.; Diallo, B. L.; McDonnell, Rachael; Pulwarty, R. S.; Svoboda, M.; Tsegai, D.; Wens, M. (Springer, 2025)
The global drought community and policy representatives gathered at the United Nations Convention to Combat Desertification’s 16th Conference of the Parties (UNCCD COP16) in Riyadh in December 2024 to discuss the urgent need for improvements in assessing and quantifying drought risks, in developing and implementing transformative solutions, and in boosting policy actions and investments. Only through unprecedented global cooperation can we facilitate pathways towards drought-resilient futures.